Performance of SD-WAN vs. MPLS networks: Evaluation in different scenarios (Innovation & Development in Engineering and Applied Science, 2026)
Software-Defined Networks (SDN) have emerged to enhance flexibility and agility in network environments by enabling management through the separation of the control plane and the forwarding plane. This separation allows networks to quickly adapt to changing environments.Meanwhile, Multiprotocol Label Switching (MPLS) networks manage traffic using a label-switching mechanism, providing key advantages in enterprise environments.This research comparatively analyzes the performance of Software-Defined Wide Area Networks (SD-WAN) and Multiprotocol Label Switching (MPLS) networks, focusing on critical parameters such as latency, jitter, bandwidth, and packet loss.For the analysis, different simulation scenarios have been designed, each subjected to a controlled traffic load. The results of each generated load are sent to a database, which is then connected to Grafana, allowing for easy data visualization through graphs.
Keywords: Networks; analysis; MPLS; SD-WAN; metrics; GNS3; quality of service